(untitled) (Homoeopathy for All, 2024)
Nasal disorders encompass a wide range of conditions affecting the nasal cavity, sinuses, and surrounding structures. They can significantly impair respiratory function, sense of smell, and overall quality of life. These disorders range from common issues like allergic rhinitis and sinusitis to more complex conditions such as nasal polyps and structural deformities. The nose plays a critical role in filtering, humidifying, and warming the air we breathe, so any disruption in its function can have widespread effects on respiratory health.